A Life of Scholarship with Santayana : Essays and Reflections - Jr., Herman J. Saatkamp (Value Inquiry Book Series, 2021)
An entire lifetime's work by Herman J. Saatkamp is collected here in A Life of Scholarship with Santayana: Essays and Reflections . From the first essay, published in 1972, to the latest, in 2017, almost fifty years of scholarship is given a fresh embodiment of expression. Saatkamp is considered by many to be the world's foremost authority on George Santayana's life and thought. Not only does this volume bring into clear relief Saatkamp's understanding of Santayana, the editing process, and genetic concerns and the future of philosophy, but it also betrays a lucid and humane understanding that aptly personifies a life spent in reflection, a discerning sense of appreciation, and an affirmation of life and learning.